Towards effective implementation of building energy efficiency codes in Tripoli, Lebanon: Key actions for enforcement - Tarek Al-Soufi Al-Sukkari; Khaled El-Daghar; Kareem Galal; Ayman Afify (Heritage and Sustainable Development)
Energy is vital for human life. However, the increasing global demand for and reliance on fossil fuels are significantly contributing to rising CO2 emissions. The Building Energy Efficiency Codes (BEECs) are a government initiative aimed at regulating CO2 emissions. BEECs support both national environmental goals and global climate change initiatives in Lebanon. The study aims to close the gap between the effectiveness of Lebanon's building energy codes and the country's environmental goals. It seeks to identify the key enforcement actions taken by the Trpl-M towards the successful implementation of the Building Energy Efficiency Code (BEEC). Tripoli was selected for its administrative independence and unique authority in enforcing building energy codes, including a dedicated technical department. This autonomy provides a valuable setting to explore compliance strategies and address regional challenges. This is achieved through an approach involving a literature review, case studies, and semi-structured interviews with employees from the Trpl-M Permit Office. The data is analyzed using a thematic analysis approach, providing a nuanced understanding of the implementation challenges within the employees' working environment. Findings suggest considering proactive design integration, third-party inspections, random compliance checks, penalties, and incentives to achieve high standards of energy efficiency and contribute to sustainable urban development and energy conservation in the region.